Original Article: Non–Small Cell Lung Cancer - Adaptive Neoadjuvant Chemotherapy Guided by 18F-FDG PET in Resectable Non–Small Cell Lung Cancers: The NEOSCAN Trial. Issue 4 (April 2016) - Chaft, Jamie E.; Dunphy, Mark; Naidoo, Jarushka; Travis, William D.; Hellmann, Matthew; Woo, Kaitlin; Downey, Robert; Rusch, Valerie; Ginsberg, Michelle S.; Azzoli, Christopher G.; Kris, Mark G.
ABSTRACT : Introduction: : Although perioperative chemotherapy improves survival in patients with resectable lung cancers, systemic recurrence remains common. Neoadjuvant chemotherapy permits response assessment and an opportunity to switch treatment regimens. Response measured by fludeoxyglucose ( 18 F‐FDG) positron emission tomography (PET) correlates with clinical outcomes better than computed tomography (CT) does. This trial assessed PET‐measured response rate to alternative chemotherapy in patients with a suboptimal PET response after two cycles of neoadjuvant chemotherapy. Methods: : This phase II study enrolled patients with resectable stage IB–IIIA lung cancers (primary tumor ≥ 2 cm and peak standard uptake value [SUVpeak ] ≥ 4.5). Patients had a pretreatment 18 F‐FDG PET/CT scan before two cycles of cisplatin (or carboplatin) plus gemcitabine (squamous cell carcinoma) or pemetrexed (adenocarcinoma) and then a repeat PET/CT scan. If SUVpeak in the primary tumor decreased by at least 35%, patients continued the initial chemotherapy. Individuals with less than a 35% PET response were switched to vinorelbine plus docetaxel. Postoperative radiotherapy was recommended to all patients with positive N2 nodes. A Simon's optimal two‐stage design was used to evaluate the primary end point of a PET Response in Solid Tumors–defined response rate to vinorelbine plus docetaxel in previously nonresponding patients. Results: : Forty patients were enrolled. Fifteen patients (38% [95% confidence interval: 38–53]) had less than a 35% decrease in SUVpeak, and 13 received vinorelbine plus docetaxel. The study met its primary end point with 10 of 15 PET metabolic responses to alternate therapy (67%). Chemotherapy toxicities never precluded surgical exploration. Conclusions: : Utilizing 18 F‐FDG PET/CT to assess response and change preoperative chemotherapy in nonresponding patients can improve radiographic measures of response. This adaptive approach can also be used to test new drugs, attempting to optimize perioperative chemotherapy to achieve better long‐term outcomes.